The Influence of The Problem-Based Learning (PBL) Model on The Learning Outcomes of Fourth Grade Students in Social Studies at SD N 040457 Berastagi - Emelda Thesalonika; Desi Sijabat (PT. Anagata Sembagi Education, 2024)
This research examines the impact of the Problem Based Learning (PBL) model on the learning outcomes of fourth-grade students in social studies at SD N 040457 Berastagi. Utilizing a quasi-experimental design, the study compares PBL-based learning methods with conventional teaching approaches. The findings reveal that students engaged in PBL-based learning demonstrate significantly improved academic performance compared to those using traditional methods. These results provide valuable insights for educators and policymakers, highlighting the effectiveness of PBL in enhancing students' understanding of social studies content. By focusing on the local context of SD N 040457 Berastagi, this research contributes to the development of teaching practices that meet students' specific needs. Furthermore, the study encourages future research to explore the potential of the PBL model across diverse educational settings, enriching the understanding of the most effective teaching methods. The primary objective of this study is to evaluate the effectiveness of the PBL model in improving students’ academic achievement and to offer recommendations to educators and policymakers regarding the use of PBL as an approach to enhance the quality of learning in schools, particularly in social studies.